Effects of gastric bypass surgery and weight loss on fertility of morbidly obese patients. Early case series - Dantas Jr, José Hipólito; Godoy, Eudes Paiva; Andrade, George Anderson da Penha; Azevedo, George Dantas (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2012)
Purpose: The aim of this study was to assess initial outcomes of effects of large weight loss after gastric bypass ssurgery on male fertile profile. Methods: Eight male morbidly obese were submitted to Roux-en-y gastric bypass and assesse before and six months after the procedure with hormonal reproductive dosage and seminal analysis both compared with the BMI. The hormonal profile consiste in total testosterone (TT), follicle-stimulating hormone (FSH) and luteinizing hormone(LH). The points examined in seminal analysis were sperm concentratio in million/ml and motility. Results: The results did not appoint to the perfect correlation of weight loss and seminal analysis. Otherwise , the sharp weight loss was responsible for the increasing on the TT levels in all patients submitted to the surgical treatment. No differences were observed on FSH and LH levels. Conclusions: Weight loss can improve the reproductive hormone profile, but this study showed that a greater number of cases to make the analysis more robust is need.